"A SURVEY OF PREVALENCE OF ORNITHODORUS TARTAKOVSKYI AND ITS INFECTION RATE WITH BORRELIA LATYCHEVI IN SARAKHS COUNTY,KHORASSAN PROVINCE " - N.Piazak; M.A. Seyedi Rashti; M. Assmar (Iranian Journal of Public Health, 2000)
This study was carried out to investigate Borrelia latychevi infection in Omithodorus tartakovskyi in the area surrounding Sarakhs County. Ten percent of the countryside was surveyed for a year and a half from the winter of 1996 to autumn of 1998, in 13 separate field trials. In the nine rural areas inspected, 135 burrows of rodent, terristerid birds and turtles were examined by destruction process. In village areas of Tajan, Sarakhs, Khangiran and Golbibi, respectively, 80%, 26.6%, 16.6% and 13.3% of burrows contained ticks. In the areas of Polkhatoon and Marzdaran no ticks were collected, 200 out of the ticks were studied for infection rate of Borrelia latychevi by direct blood engorgement. Only 30% of the studied ticks were capable of causing Caucasian tick-borne relapsing fever in infant mice, and the rate of infection of Ornithodorus tartakovskyi with Borrelia in Tajan area was 36%.